Enzymatic protein depalmitoylation by acyl protein thioesterases. (7th April 2015) - Lin, David T.S.; Conibear, Elizabeth
Abstract : Protein palmitoylation is a dynamic post-translational modification, where the 16-carbon fatty acid, palmitate, is added to cysteines of proteins to modulate protein sorting, targeting and signalling. Palmitate removal from proteins is mediated by acyl protein thioesterases (APTs). Although initially identified as lysophospholipases, increasing evidence suggests APT1 and APT2 are the major APTs that mediate the depalmitoylation of diverse cellular substrates. Here, we describe the conserved functions of APT1 and APT2 across organisms and discuss the possibility that these enzymes are members of a larger family of depalmitoylation enzymes.